An IOT Security Based Electronic Aid for Visually Impaired detection with Navigation Assistance System - R.Aiyshwariya Devi , U.Indumathi , S.Radha Rammohan , N. Keerthana , S.Shobana (International Journal of Advanced Science and Technology, 2020)
The paper present an electronic aid for visually impaired people to navigate them the blind canewill find the potholes and obstacles and notify the visually impaired through the voice command andthey active location will be share to care taker through the text message the voice command will bepass through the headphone .In involves an Arduino IDE to detect the movement of the blind peoplewhen they walk and a microcontroller works and will be a speech output. The visually impaired cantravel individuals without the guides.